The effect of arm exercise on the energy cost of StairMaster stepping in males - Doronio, Damian R. (My University, 1995)
This study compared the metabolic responses of StairMaster 4009PT (SM) stepping with the addition of upper body exercise (WA) using the UB Sports Fitness Trainer (UBSFT) td SM stepping with no arm use (WOA). Step depth WA and WOA were also biomechanically analyzed. Twenty-two active males (19-32 yrs) completed 2, 20-minute tesks on the SM. The tests consisted of stepping at 4, 5-min workrates ( 3 , 5, 7, and 9). Two alternating vrorkrates required arm usage on the first testing day and the other two w~rkrates on the second testing day. During all tests expired air was analyzed using open circuit spirometary, MR and RPE were recorded, and step depth was videotaped.
Keywords: Step aerobics, Physiological aspects.; Energy metabolism.; Stairmaster 4000PT (Exercise machine), Physiological effect.